Minat Berwirausaha Ditinjau Dari Kepribadian DanLingkungan Keluarga Pada Mahasiswa PendidikanAkuntansi Fakultas Keguruan Dan IlmuPendidikan Universitas Muhammadiyah - Sintawati, Anindya Fara, Dr. Wafrotur Rohmah, MM (2016)
The purpose of this research are: 1) To determine whether there is influence of personality on the interest in entrepreneurship. 2) To determine whether there is influence of family environment on interest in entrepreneurship. 3) To determine whether there is influence of family environment on the personality and interest in entrepreneurship. This research is a descriptive research with quantitative approach to drawing conclusions through statistical methods. The population in this study were all students of the Faculty of Accounting Education Teaching and Education University of Muhammadiyah Surakarta 2013/2014 force numbering 182 students, with a sample of 123 students using simple random sampling technique. Methods of data collection is questionnaire and documentation. Questionnaire first be tested to determine the level of validity and reliability. Test requirements analysis in the form of normality test, linearity and multicollinearity, to engineering data analysis using multiple linear regression analysis, t test, F test, the coefficient of determination as well as the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 2,144+ 0,462X1 + 0,483X2. The conclusion that can be drawn from this equation are: 1) "There is the influence of personality on the interest in entrepreneurship" is acceptable. This is proven through hypothesis test (t test), which is known that tcount> ttable namely 5.203> 1.979 and the significance value <0.05 is 0,000 effective contribution (SE) of 16.43%. 2) "There is the influence of family environment on entrepreneurship interest" may be accepted based on hypothesis test (t test), which is known that tcount> ttable namely 6.891> 1.979 and the significance value <0.05 is 0.000 with the effective contribution of 21.57% , 3) "There is the influence of family environment on the personality and interest in entrepreneurship" unacceptable demonstrated through F test, which indicates the value of F> Ftable is 36.801> 3.07 and a significance value <0.05 is 0.000 with a coefficient of determination (R2) of 0.380 or 38%, while 62% are influenced by other variables outside the study.